PENGARUH KONSUMSI KACANG MERAH TERHADAP PENGOBATAN ANEMIA PADA IBU HAMIL DI PUSKESMAS SENDANA KOTA PALOPO - Andi St. Umrah; Andi Kasrida Dahlan (Lembaga Penerbit dan Publikasi Ilmiah (LPPI) Universitas Muhammadiyah Palopo, 2018)
Red beans are one of the foods high in fiber. Red beans are also high in nutrients that improve a healthy body. The content of iron, folic acid, calcium, carbohydrate and high protein in red beans benefits body health, especially for pregnant women to prevent the occurrence of anemia during pregnancy. This study aims to determine the effect of red beans on the treatment of anemia in pregnant women to avoid anemia.Research Method: Quantitative analysis with the one group pre-test post-test design. The samples in this study were all pregnant women who experienced anemia at the Puskesmas Sendana Palopo City between May and June in 2017, accounting for 30 people. Sampling used was total sampling technique. Data analysis techniques used the test t-test , which was one-sample test.Result: Based on the research, it obtained ρ = .002. This means that there is an effect of consumption of red beans on the treatment of anemia in pregnant women at the Palopo City Sendana Health Center, with mean Hb levels before treatment was 9.7 ± 0.9, and Hb levels after treatment was 12.5 ± 1, 1. This suggests that an increase in Hb after treatment by a mean difference was 2.8, so red beans can be used as a traditional medicine to increase Hb levels during pregnancyConclusion: there are influences of pregnant women who consume red beans on the treatment of anemia. Keywords: Red Beans, Anemia, Pregnant Women